Strategi Pengembangan Agrowisata di Banjar Timbul, Desa Pupuan, Kecamatan Tegallalang, Kabupaten Gianyar - KUSUMA, DEWA GEDE ANGGA; PITANA, I GDE; DIARTA, I KETUT SURYA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.2, Desember 2024, 2024)
Agrotourism Development Strategy in Banjar Timbul, Pupuan Village, Tegallalang District, Gianyar Regency.  Agrotourism or agricultural tourism is defined as a series of tourism travel activities that utilize the location or agricultural sector from the initial stages of production to the acquisition of agricultural products. Agro-tourism in Banjar Timbul is managed by a traditional village through BUPDA (Baga Utsaha Padruen Desa Adat) under the name Kampung Wisata Timbul. The lack of tourist visits to Banjar Timbul has caused this agro-tourism to seem to be running in place. The method used in this study was an in-depth interview method using a questionnaire and FGD assistance. Interview data were then analyzed using the IFAS matrix to obtain internal factors, EFAS to obtain external factors, to obtain strategic formulation using SWOT analysis, and the QSPM matrix to obtain strategic priorities.